Inhibitory effect of 2-Nitroacridone on corrosion of low carbon steel in 1 M HCl solution: An experimental and theoretical approach - Jeenat Aslam; Ruby Aslam; Irfan Hussain Lone; Nagi R.E. Radwan; Mohammad Mobin; Afroz Aslam; Mehtab Parveen; Ajab Abdullah Al-Freedi; Alaa Awad Alzulaibani (Journal of Materials Research and Technology, 2020)
The present study aims to explore the effect of 2-nitroacridone, an antimicrobial compound, on low carbon steel (LCS) corrosion in acid solution (1 M HCl). The compound was tested at various concentrations (0.001−10 mM) and five temperatures (25, 35, 45, 55, and 65 °C) to determine the optimal concentration and temperature range for the best corrosion inhibiting effect. In evaluating the inhibition efficiency, weight loss measurement, potentiodynamic polarization measurement, electrochemical impedance spectroscopy, SEM/EDAX/AFM and DFT measurements were used. The inhibition efficiency increases with the increase in concentration and decreases with temperature. The maximum inhibition efficiency was found (94.96%) at 25 °C in the presence of 5 mM concentration of the studied compound. The various adsorption isotherms were also explored to find the best fit, which was found to obey the Langmuir adsorption isotherm. The thermodynamic parameters (Ea, Kads, ΔG°ads) have also been calculated and discussed. The potentiodynamic polarization study revealed that 2-nitroacridone behaved as a mix-type of inhibitor that predominantly inhibited the anodic reaction. Moreover, a correlation between the inhibition efficiency of the studied compound and certain molecular parameters were determined by quantum chemical computations.